2006
DOI: 10.1111/j.1365-2826.2006.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clocks: Setting Time By Food

Abstract: In mammals, daily rhythms in behaviour and physiology are driven by a circadian timing system comprised, in a hierarchical way, of a master pacemaker in the suprachiasmatic nuclei (SCN) of the hypothalamus and of peripheral oscillators in most body cells. At the molecular level, in both the SCN and peripheral oscillators, the circadian clock mechanism is built from interconnected feedback loops in gene expression that operate in a cell-autonomous and self-sustained fashion. The SCN clock is mainly entrained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
189
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(195 citation statements)
references
References 111 publications
(191 reference statements)
2
189
1
3
Order By: Relevance
“…Under periodic food-availability conditions, this prediction is manifested in anticipatory bouts of locomotor activity and body temperature (Mistlberger, 1994;Challet et al, 1997;Stephan, 2002). This process seems to be driven by a food-entrainable oscillator independent of the main, light-entrainable clock located in the SCN (Stephan, 2002;Mendoza, 2007). Our previous investigation in a domestic species, the sheep, demonstrated the strong impact of the periodic food availability on the daily rhythms of total activity (Piccione et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Under periodic food-availability conditions, this prediction is manifested in anticipatory bouts of locomotor activity and body temperature (Mistlberger, 1994;Challet et al, 1997;Stephan, 2002). This process seems to be driven by a food-entrainable oscillator independent of the main, light-entrainable clock located in the SCN (Stephan, 2002;Mendoza, 2007). Our previous investigation in a domestic species, the sheep, demonstrated the strong impact of the periodic food availability on the daily rhythms of total activity (Piccione et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
“…The rhythmic production of the pineal hormone melatonin, which is a part of the timekeeping system, is also highly photoperiod-dependent, both in nocturnal and in diurnal animals; the high nocturnal melatonin production is shorter on long summer than on short winter days (Illnerová , 1991). Food availability for only a limited time each day is also a zeitgeber signal for mammalian circadian rhythms (Stephan, 2002;Mendoza, 2007). Interestingly, recent evidence indicates that clock gene expression in the liver and some other peripheral tissues become entrained to periodic meals whereas clock gene expression in the SCN does not appear to be affected by timed feeding (Damiola et al, 2000;Stokkan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…When food is available only for a limited time each day, rats increase their locomotor activity 2 to 4 h before the onset of food availability (Stokkan et al, 2001). This food anticipatory behavior occurs in other mammals, including goats, and is often accompanied by increases in body temperature, secretion of corticosterone, gastrointestinal motility and activity of digestive enzymes (Stokkan et al, 2001;Piccione et al, 2003;Mendoza, 2007;Bass and Takahashi, 2010).…”
Section: The Circadian Systemmentioning
confidence: 99%
“…When food is available only for a limited time each day, rats increase their locomotor activity 2 to 4 h before the onset of food availability (Stokkan et al, 2001). This food anticipatory behavior occurs in other mammals, including goats, and is often accompanied by increases in body temperature, secretion of corticosterone, gastrointestinal motility and activity of digestive enzymes (Stokkan et al, 2001;Piccione et al, 2003;Mendoza, 2007; Bass and Takahashi, 2010).Microarray analysis of the impact of two acute restricted feeding regimens (4 v. 10 days) with identical body weight (BW) loss (19%) on hepatic gene expression in rats showed that the two regimens led to distinct patterns of differentially expressed genes in liver. Transcription profiles of 4-day restricted rats suggested that they were in an early phase of metabolic adaptation to feed restriction.…”
mentioning
confidence: 99%
“…Nevertheless, the SCN clockwork and its photic responses can be modulated by nutritional cues (Castillo et al, 2004;Challet et al, 2003;Lamont et al, 2005;Mendoza et al, 2005b). Moreover, restricted feeding schedules (Mendoza, 2007;Waddington-Lamont et al, 2007) and other non-photic cues, like methamphetamine administration (Iijima et al, 2002), have also been shown to influence behaviour and physiology outside the SCN. Thus, even if the SCN is undoubtedly the master circadian clock, other brain regions and many other cells around the body express clock genes and are capable of sustained clock gene 0928-4257/$ -see front matter Ó 2007 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%